Compassionate Homicide - Michal Buchhandler-Raphael (Washington University Law Review, 2020)
Ample psychological studies demonstrate that emotions provide reasons for action and are powerful drivers of a host of behaviors, including criminal acts. Studies further establish that experiencing intense emotions might impair actors’ judgment and decision-making, sometimes culminating in committing homicide. Existing criminal law doctrines only partially correspond to these findings. They recognize mostly anger and fear as underlying the excuses of provocation, imperfect self-defense, and duress by mitigating murder charges to manslaughter or otherwise excusing offenders. Currently, however, no doctrine recognizes compassion as a basis for mitigation. Under existing laws, an actor who intentionally kills a terminally ill or severely disabled close family member, wholly out of compassion for the victim, commits the crime of murder. The actor’s motive to end the victim’s suffering is irrelevant for determining the scope of criminal responsibility. In recent years, legal scholars have developed a new field of study focusing on the interplay between law and the emotions, including among others, in the realm of criminal law. This Article contributes to existing literature in this area by suggesting that compassion is yet another emotion that may trigger certain actions. Advocating the adoption of a statutory affirmative defense that is grounded in compassion, this Article argues that recognizing this excuse is consistent with the rationales and reasoning underlying criminal law’s recognition of existing emotion-based excuses. This Article develops the theoretical and doctrinal bases for endorsing a compassion-based partial excuse by advancing three arguments. First, it contends that experiencing compassion towards a close family member might affect an actor’s judgment and decision-making, motivating them to kill. Second, it argues that from a policy-based perspective, recognizing a compassion-based excuse is normatively warranted because while the killing is neither justified nor fully excused, it is an understandable reaction given the circumstances the actor was facing. Third, this Article outlines some necessary constraints on the scope and limits of the partial excuse to ensure that it is applicable only in appropriate cases, where actors normatively deserve mitigation.
Keywords: Compassionate homicide; Criminal law; Mitigation; Criminal defense; Law and emotion; Affirmative defense